Effect of alpha-hederin and sapindoside B on hepatic microsomal cytochrome P-450 in mice - Shi Jing-Zhen; Liu Geng-Tao (Acta Pharmacologica Sinica, 2016)
AIM: To study the relation between the effect of alpha-hederin (Hed) and sapindoside B (Sap B) on cytochrome P-450 and their hepatoprotection. METHODS: Mice were given sc Hed, Sap B, as well as a mixture of Hed + Sap B (1:1.5), and hepatic microsomal cytochrome P-450 was examined. RESULTS: Hed 20 mg.kg-1, Sap B 20 mg.kg-1 and Hed + Sap B 20 mg.kg-1 sc, reduced hepatic P-450 content by 40%, 55% and 50%, respectively. The effect of the saponins on P-450 was reversible, as P-450 level returned to normal after 3 d. Phenobarbital (Phe) 50 mg.kg-1 ip increased P-450 2.5-fold, the Phe-induced P-450 was inhibited 50% by Hed + Sap B. No inhibitory effect was seen when liver microsomes were incubated with Hed + Sap B in vitro. CONCLUSION: The hepatoprotective effects of Hed and Sap B were at least in part, due to its suppressive effect on liver cytochrome P-450.